2019
DOI: 10.1097/ta.0000000000002202
|View full text |Cite
|
Sign up to set email alerts
|

Association between age and acute respiratory distress syndrome development and mortality following trauma

Abstract: Background: Improved understanding of the relationship between patient age and acute respiratory distress syndrome (ARDS) development and mortality following traumatic injury may help facilitate generation of new hypotheses about ARDS pathophysiology and the role of novel treatments to improve outcomes across the age spectrum. Methods: We conducted a retrospective cohort study of trauma patients included in the National Trauma Data Bank who were admitted to an intensive care unit from 2007-2016. We determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 53 publications
3
39
1
1
Order By: Relevance
“…This is not surprising as men are supposedly more exposed to environmental factors than women [23]. The age-adjusted MRRSDs were higher in the > 65 years age group, which has also been reported in various geographical regions [14][15][16].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This is not surprising as men are supposedly more exposed to environmental factors than women [23]. The age-adjusted MRRSDs were higher in the > 65 years age group, which has also been reported in various geographical regions [14][15][16].…”
Section: Discussionsupporting
confidence: 61%
“…Meanwhile, Adegboye et al found that interventions to minimise mortality from the Middle East respiratory syndrome (MERS) coronavirus had a particular focus on individuals with co-morbidities, workers outside the health-care field and patients without clinical experience [12], and Chowell et al noted a high geographic heterogeneity in the impact of the 1918-1919 influenza pandemic mortality in Spain [13]. Other studies have confirmed a significantly robust relationship between MRRSDs and ageing [14][15][16]. Lai et al [17] incorporated stochastic processing of environmental and social variables that interact in space and time to affect the patterns of disease transmission in a community.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have reported age as an independent predictor of mortality in ARDS (40,41). It should be emphasized that substantial heterogeneity exists within the syndrome and non-linear associations between age and mortality have been reported within specific ARDS phenotypes [i.e., trauma; (42,43)]. When considering the trauma-ARDS cohort, the highest burden of mortality has been shown to exist at the extremes of age (42,43).…”
Section: Clinical Characteristics Of Aging In Ardsmentioning
confidence: 99%
“…It should be emphasized that substantial heterogeneity exists within the syndrome and non-linear associations between age and mortality have been reported within specific ARDS phenotypes [i.e., trauma; (42,43)]. When considering the trauma-ARDS cohort, the highest burden of mortality has been shown to exist at the extremes of age (42,43). A large retrospective review of a national trauma database (n = 1,297,190) reported the ARDSrelated mortality was highest in those ≥80 and ≤4 years (42).…”
Section: Clinical Characteristics Of Aging In Ardsmentioning
confidence: 99%
See 1 more Smart Citation